Evaluation from an Environmental Perspective of Soybean Cultivation in the State of Maranhão - Rabelo, Weslley Phelix Silveira; Cruz, Glauber; Silva, Arthur Vinicius Sousa; Gomes, Wolia Costa (Ciência e Natura, 2022)
Agribusiness is a fundamental component in the economic growth of a country. In Brazil, for example, agricultural activity is considered a major part of the economy and is carried out on a large scale, requiring professional execution so that the expected results can be achieved. This study investigates the environmental impacts generated in the soybean crop production process, namely the planting, generation process and residue disposal in Maranhão State, specifically in Balsas city (MA). An online questionnaire (Google Forms) and face-to-face interviews were used, which were validated and tested to quantitatively and qualitatively measure the presence of environmental impacts resulting from the soybean production process. Results revealed the existence of a unanimous perception among the interviewees about sustainability in the soybean production process, especially regarding the resulting problems, including for example, deforestation, erosion and intoxication among other factors. The respondents also demonstrated knowledge about the sustainability concepts associated with the environmental aspects and the existence of the residue control issues generated in this production process. In view of the visible results, it can be concluded strongly that there are numerous environmental impacts from the residue generation and soybean cultivation processes.